1999
DOI: 10.1002/(sici)1097-0215(19990219)84:1<49::aid-ijc10>3.3.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

p16 inactivation in small‐sized lung adenocarcinoma: Its association with poor prognosis

Abstract: p16, an inhibitor of cell cycle machinery, is frequently inactivated in non-small cell carcinoma of the lung (NSCCL).To clarify the significance of p16 inactivation in the progression of lung adenocarcinoma, we immunohistochemically evaluated p16 protein status and Rb, p53 and cyclin D1 expression in 51 surgically resected adenocarcinomas that were less than 3 cm in diameter (median follow-up period: 52.5 months). Twenty-one of 51 adenocarcinomas showed negative immunostaining for p16. Twenty adenocarcinomas w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2003
2003
2006
2006

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
3
0
1
Order By: Relevance
“…Expression of the p16 gene is decreased by hypermethylation of the promoter region and LOH at chromosome 9p21 in accord with the multiple-step progression of lung adenocarcinoma, and these alterations are closely associated with poor prognosis. [23][24][25][26][27] In adenocarcinoma of the lung, diffuse and strong p53 expression suggested that the p53 gene mutation is inversely correlated with tumor differentiation. 27 According to the results of these immunohistochemical data, PA seems to be a more advanced phenotype than BAC.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of the p16 gene is decreased by hypermethylation of the promoter region and LOH at chromosome 9p21 in accord with the multiple-step progression of lung adenocarcinoma, and these alterations are closely associated with poor prognosis. [23][24][25][26][27] In adenocarcinoma of the lung, diffuse and strong p53 expression suggested that the p53 gene mutation is inversely correlated with tumor differentiation. 27 According to the results of these immunohistochemical data, PA seems to be a more advanced phenotype than BAC.…”
Section: Discussionmentioning
confidence: 99%
“…One study has shown an association between upregulation of expression and a well-differentiated phenotype in colorectal cancer [23]. Furthermore, loss of p16 expression has been associated with a poorly differentiated phenotype in other malignancies [13,15,19,50]. A possible reason for this association is that tumors with loss of p16 expression have deregulated cell cycle progression and this in turn may lead to rapid cell turnover.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of p16 expression is an important step in promoting carcinogenesis as clearly evidenced by its association with a number of malignant diseases [11][12][13][14][15][16][17][18]. Importantly, loss of p16 expression has been associated with clinical stage, grade, and prognosis in some cancers [13,[15][16][17][19][20][21]. Loss of p16 expression has also been described in colorectal cancer in both tumors and cell lines [11,[22][23][24]; however, the incidence and clinicopathological significance of absent p16 expression in colorectal cancer have not been determined.…”
Section: Introductionmentioning
confidence: 99%
“…Οι αλλοιώσεις αυτές θεωρούνται πρώιμες στην καρκινογένεση του πνεύμονα[23,154]. Ο προγνωστικός ρόλος του δεν είναι πλήρως αποσαφηνισμένος[155,156].…”
unclassified